Robotten – Den hundredårige der kom ind på scenen og ikke forsvandt - Juel Henrichsen, Peter (Sprog i Norden, 2022)
The term ’robot’ was invented 100 years ago. In this short essay, we comment on the development of the humanoid robot, its impressive motoric and analytical capabilities in contrast to its exceedingly poor conduct of natural language.